Assess the level of damage to the coral reef ecosystem based on substrate coverage on Bira Island, Kepulauan Seribu, Indonesia (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Komala R, Noer MI, Miarsyah M, Widyartini DS, Handayani. 2024. Assess the level of damage to the coral reef ecosystem based on substrate coverage on Bira Island, Kepulauan Seribu, Indonesia. Biodiversitas 25: 971-977. Coral reefs are coastal ecosystems that have an important ecological and economic role. Environmental pressures cause damage to ecosystems and decrease coral biodiversity. This study aims to analyze the level of damage to coral reef ecosystems based on substrate cover and obtain the latest information on coral reef ecosystem resources. The study employs a descriptive method with a survey design, utilizing Underwater Photo Transect (UPT) sampling at various depths along the coastline. The data is analyzed using Coral Point Count with Excel extension (CPCe) for substrate cover percentage and the Shannon-Wienner index for coral diversity. The findings reveal nine categories of basic substrate cover, with living hard corals constituting 32.51%, indicating a fairly damaged state. Coral resources are identified across 53 genera and 15 families, exhibiting medium diversity across stations and depths. The study highlights the need to monitor environmental threats that could further damage coral reefs and decrease diversity. The coral reef ecosystem in Bira Island is in a relatively damaged condition, with a decline in coral biodiversity, indicating an imbalance in the ecosystem. Several recommended steps include implementing coral restoration programs, monitoring coral growth, establishing critical coral habitat protection zones, and conducting conservation efforts.